23.9k views
0 votes
PLEASE HELP 25 POINTS

PLEASE HELP 25 POINTS-example-1

1 Answer

7 votes

Hello from MrBillDoesMath!

Answer:

First term = S(1) = 1

Common difference = S(n+1) - S(n) = 1 -6n

t(n) value: can't answer this as I don't know what t(n) refers to,



Discussion:

Let S(n) = 4n - 3n^2

First term:

S(1) = 4(1) - 3(1)^2 = 4 - 3 = 1


Common difference:

S(n+1) - S(n) = ( 4(n+1) - 3 (n+1)^2) - (4n - 3n^2)

= (4n + 4 - 3n^2 -6n -3) - 4n + 3n^2

(now cancel common terms)

= -6n + 4 - 3 = -6n + 1


S(n+1) = S(n) -6n + 1


Thank you,

MrB

User Peter Van De Put
by
5.8k points